Utilizing Haiku as a Learning Reflection: Students’ Perception - Fera Sulastri; Melisa Sri; Sitti Syakira (STAI Hubbulwathan Duri, 2022)
Haiku, the 5-7-5 syllables of Japanese poetry, has been known widely as a tool to express voice and reflect on what happens to personal life experiences. Therefore, this study aimed to uses Haiku as a learning reflection on the Children’s Literature Class. Two questions were addressed to examine (1) Students’ perception of writing Haiku as a learning reflection and (2) challenges in writing Haiku as a learning reflection. Descriptive case A descriptive case study was used as the research methodology, while 49 students taking children's literature class participated. In data collection, this study used open-ended questionnaires given to all participants, while semi-structured interviews were delivered to 11 representative students. Students’ Haiku also were used as additional data. In addition, the data were analyzed thematically, using the framework of Braun and Clark (2006) and students’ Haiku were analyzed through document analysis. The findings show that students find that writing haiku as a learning reflection is fun and interesting. It also promotes their creativity in writing. However, since Haiku is fixed verse poetry, it does not cover students’ ideas of expressing their experience of learning freely and effectively. Eventually, Haiku still supports creativity, not effectiveness.